1993
DOI: 10.1080/00039896.1993.9940371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Heart Rate and Ventilation for Epidemiologic Studies

Abstract: Estimation of pulmonary exposure and dose in air pollution epidemiology has been impaired by the lack of methods for directly measuring ventilation in ambulatory subjects. Heart-rate monitoring offers an approach to estimate ventilation by using ventilation-on-heart-rate (VE-HR) regressions established during exercise testing to estimate ventilation in the field. Conventional methods and protocols for testing were used to evaluate the relationship between VE and HR during three tasks: (1) exercising on a cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
6
28
0
1
Order By: Relevance
“…2 ) in Table 3 are lower than past reported values from lab ergometer studies (1,8), which is attributable to greater measurement error in the indirect field measurements of 7 http://certification.acsm.org/metabolic-calcs ventilation rate (using the BioHarness chest strap with spirometer calibrations) than the direct laboratory measurements of ventilation rate (using facemasks and pneumotachometers).…”
Section: Ventilation and Heart Ratementioning
confidence: 63%
See 2 more Smart Citations
“…2 ) in Table 3 are lower than past reported values from lab ergometer studies (1,8), which is attributable to greater measurement error in the indirect field measurements of 7 http://certification.acsm.org/metabolic-calcs ventilation rate (using the BioHarness chest strap with spirometer calibrations) than the direct laboratory measurements of ventilation rate (using facemasks and pneumotachometers).…”
Section: Ventilation and Heart Ratementioning
confidence: 63%
“…Low-ranged values of the lṅ~̇ slope in these data could be attributed to a muted ventilatory response to dynamic power output. 8 Zoladz et al (26) found that ̇2 increases non-linearly at power output over 250W 9 the amount of energy derived from atmospheric oxygen that is translated to external work, previously defined as 10 A common model uses the oxygen uptake efficiency slope (OUES), which is defined as ̇2 = • 10̇+ .…”
Section: Comparison With Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…VĖ is difficult to measure in field studies due to some constraints such as discomfort for the user and the need for an elevated number of instruments to perform the evaluation of a representative number of individuals. However, VĖ can be estimated by measuring HR in fitness classes because HR is easily measured and is a good predictor of VĖ (Mermier et al, 1993;Zuurbier et al, 2009). Once HR is mainly influenced by oxygen consumption and the correlation between oxygen consumption and VĖ is high, HR and VĖ are expected to be strongly associated.…”
Section: Determination Of Vė During Fitness Classesmentioning
confidence: 99%
“…Although the author emphasized that, if the focus of the study is at the individual level, an overall equation of the whole group may result in substantial differences in estimated VĖ at the individual level. In the same way, Mermier et al (1993) indicated that it is necessary to calculate individual regression equations due to the individual variability among HR and VĖ.…”
Section: Estimation Of the Vė In Fitness Classesmentioning
confidence: 99%